Problem-Based Learning in Civics Education (PKN): A Classroom Action Research in Indonesia - Okta Rosfiani; Sri Wahyuni; Miko Dwi Irawan; Wahyu Nurdianto; Angkasa Putra Mandala Guna (Lembaga Riset dan Inovasi Masyarakat Madani, 2024)
This study investigates the effectiveness of the Problem-Based Learning (PBL) model in improving learning outcomes in Civics Education (PKn) for Grade II students at SDS Islam An-Nuriyah. Conducted as Classroom Action Research (CAR) using the Kemmis & McTaggart model, the study was carried out in three stages: pre-cycle, Cycle I, and Cycle II. The data were collected through observation, field notes, tests, and documentation and analyzed descriptively using percentages to measure student progress. The pre-cycle results revealed that only 68.8% of students met the Minimum Completion Criteria (KKM), indicating a need for intervention. After implementing PBL in Cycle I, student learning outcomes improved, with 78.13% of students meeting the KKM. Adjustments were made for Cycle II, including refining teaching techniques and incorporating additional learning media. By the end of Cycle II, 96.88% of students met the KKM, reflecting significant progress in understanding the concepts of deliberation, collaboration, and critical thinking. This study demonstrates that the PBL model fosters active participation, collaborative learning, and critical problem-solving among primary school students, leading to improved academic performance. The findings suggest that PBL can serve as an innovative approach to enhance engagement and achievement in primary education. Future studies are recommended to explore its long-term impact on civic competence and its application across diverse educational settings.